Quality of life in idiopathic pulmonary fibrosis in Latin American countries - H. Aguilar-Duran; M. Fernández; M. González-García; E. Rincón-Alvarez; M. Alberti; F. Caro; E. Tavera; E. Vásquez; N. Cortez; M. Salinas; M. Florenzano; C. Florestano; et al. (BMC Pulmonary Medicine)
Abstract Background Idiopathic pulmonary fibrosis (IPF) is the most common Interstitial Lung Disease (ILD). It is characterized by dyspnoea and a progressive decline in lung function, which negatively affects life. This study aimed to evaluate Health-Related Quality of Life (HRQoL) in IPF patients in Latin American countries. Methods Six countries (Argentina, Bolivia, Colombia, Chile, Mexico, and the Dominican Republic) enrolled patients with IPF. They answered the Saint George’s Respiratory Questionnaire for Idiopathic Pulmonary Fibrosis (SGRQ-I) and the Hospital Anxiety and Depression Scale (HADS). Demographic characteristics, the Torvan index, and a lung function test were also assessed. IPF was diagnosed according to the ATS/ERS/JRS/ALAT 2018 criteria. Results We enlisted 75 patients diagnosed with IPF; 81% were male, with an average age of 74 ± 7. The total SGRQ-I score was 49 ± 23, with a higher score in the activity domain of 70 ± 23. Torvan index average was 17 ± 6. We found that 28% presented anxiety and 35% depression. Besides, we observed that patients requiring oxygen had a worse quality of life (total SGRQ-I 62 ± 22 vs. 45 ± 22, p = 0.003) without finding differences in antifibrotic therapy. We did not find differences in HRQoL when dividing groups according to their altitude above sea level, except for a higher frequency of anxiety in patients living at sea level. Conclusions We found similar data compared to those reported in real-life European populations. We also found that anxiety and depression are prevalent. However, they are often underdiagnosed and, therefore, left untreated.